Chromium substituted copper ferrites via gluconate precursor route. Issue 4 (May 2015) - Mindru, Ioana; Gingasu, Dana; Patron, Luminita; Marinescu, Gabriela; Calderon-Moreno, Jose Maria; Diamandescu, Lucian; Preda, Silviu; Oprea, Ovidiu
Abstract: CuFe2− x Cr x O4 spinel (0≤ x ≤2) powders were synthesized by a soft chemistry method—the gluconate multimetallic complex precursor route. The complex precursors were characterized by elemental chemical analysis, infrared (IR) and ultraviolet–visible (UV–vis) spectroscopy, thermal analysis and Mössbauer spectroscopy. The oxide powders were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), IR, Raman and Mössbauer spectroscopy. It was shown that the structure, morphology and magnetic properties of the obtained spinel powders depend on the concentration of Cr 3+ ion. The XRD of the chromium substituted copper ferrite powders calcined at 700 °C/1 h indicated the formation of a cubic spinel type structure for x =0.5, 1.0 and a tetragonal structure for x =0, 0.2, 2. The crystallite size ranged from 19 nm to 39 nm. The Mössbauer spectroscopy revealed the site occupancy of iron ions, relative abundance and internal hyperfine magnetic fields in both tetrahedral and cubic CuFe2− x Cr x O4 spinels.